Peningkatan Kemampuan Menendang dan Menahan Bola dengan Model Active Learning Kombinasi Small Sided Game - Ihsan, Muhammad; Suhartina, Suhartina (IAIN Parepare, 2024)
The objectives of this study are to describe 1) the improvement in ball-kicking skills using the active learning model combined with small-sided games in class VII-4 students of SMP 9 Parepare, and 2) the improvement in ball-stopping skills using the same model. The research method used is classroom action research with two cycles. The data collection techniques used are observation and tests. The results showed that 1) the application of the active learning model combined with small-sided games in soccer lessons conducted over two cycles improved the ball-kicking skills of class VII-4 students. This was evident from the increase in the average ball-kicking ability of students from 64.1 initially to 73.7 (in cycle 1), and further increasing to an average of 82.4 in the second cycle, with a KKM achievement rate of 92.5%. 2) The active learning model combined with small-sided games improved the ball-stopping skills of class VII-4 students at SMP 9 Parepare. This was based on the increase in the average student score, which before the intervention was only 64.5, increasing to an average of 73.45 (cycle 1), and further increasing in cycle 2 to an average of 80.86, with a KKM achievement rate of 85.1%. The improvement in students' psychomotor scores was accompanied by improvements in their affective and cognitive scores. In the affective aspect, students became more active in learning, more confident in performing in front of their peers, and more enthusiastic in asking questions.